Contribution of Mental Strength to Academic Stress in High School Students - Nabila Rachman (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2023)
In the learning process in high school, students have the potential to experience stress due to task demands and their inability to complete learning tasks. Stress in the learning process is called academic stress. Various causes of academic stress include assignment demands that are considered too heavy, low test scores, a large number of assignments, and the surrounding environment. In other words, high school students need mental toughness in studying. The aim of this research is to reveal the influence of mental toughness on academic stress in high school students. This research is quantitative research. The subjects in this study were 65 class XI high school students in City 'X